2009
DOI: 10.1007/s00428-009-0871-2
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma with mixed features of papillary and clear cell cytomorphology: a fluorescent in situ hybridization study

Abstract: We performed fluorescent in situ hybridization (FISH) to investigate the numeric change of chromosomes 7, 17, and Y and loss of chromosome 3p in "papillary renal cell carcinomas (RCC) with extensive clear cell changes (CCC)." Consecutive cases of RCC over a 12-year period were reviewed to identify "papillary RCC with extensive CCC." Immunostaining for cytokeratin 7 and alpha-methylacyl-CoA racemase (AMACR) and FISH for chromosomes 7, 17, Y, and 3p were applied. Of the total of 521 RCC retrieved, there were 49 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Some of these tumors are clear cell renal cell carcinomas with focal papillary formations, while other tumors have papillary architecture with extensive (5-100%, median 10%) clear cell change but variable immunoreactivity for cytokeratin 7 and α-methylacyl-CoA racemase. These tumors are in need of further studies [10][11][12].…”
Section: Discussionmentioning
confidence: 95%
“…Some of these tumors are clear cell renal cell carcinomas with focal papillary formations, while other tumors have papillary architecture with extensive (5-100%, median 10%) clear cell change but variable immunoreactivity for cytokeratin 7 and α-methylacyl-CoA racemase. These tumors are in need of further studies [10][11][12].…”
Section: Discussionmentioning
confidence: 95%
“…Areas of cytoplasmic clearing are sometimes present in papillary carcinoma, [11][12][13][14] creating some overlap between these two entities. In particular, 29% of tumors in this study showed a distinctive pattern of branching papillae composed of a main bulbous, rounded core with prominent fibrovascular stroma, giving rise to multiple smaller, 'budding' papillae, in contrast to the typical, more uniform branching pattern of long delicate papillae typical of papillary renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…High nuclear grade has also been well described in type 1 P-RCCs in many studies[1,4–6,10,11], in contrast to the low nuclear grade classically described. P-RCCs with optically clear cytoplasm[27] and solid growth pattern[28] have also been described. Furthermore, it has been shown that classic type 1 and type 2 morphologies may be seen in the same tumor[5].…”
Section: Discussionmentioning
confidence: 99%